Improvement of the activity of the head of an education institution in the area of making and implementing management decisions - Shalimova, I.; Shalimova, A. (Problems of Engineer-Pedagogical Education, 2020)
The article is devoted to the problem of improving the activity of heads of education institutions in terms of making and implementing managerial decisions. The managerial decision is the result of an assessment of the situation on the basis of information analysis, forecasting, optimization, choosing from the many possible options one that will best contribute to the achievement of a specific goal. The article proves that all functions of managing education institutions can be divided into three groups. The first group consists of the so-called target functions or activity goals which reveal the main directions, tasks and content of management activity in the education establishment: management of the educational process, pedagogical guidance of education, improvement of pedagogical skills, financial and economic activity. The second group of functions highlights the algorithm of actions in the control process. The third group reveals the basic social and psychological aspects of managing an education institution: orientation, motivation, cohesion, creative development, conflict prevention, stimulation, etc. The article states that a managerial decision is a component of any function of managerial activity of the head of any organization, including organizations of education. A component composition of the management decision structure has been identified, which includes the following components: the decisionmaker, the subject of the decision, the object of the decision, which is the problem that needs to be solved. The procedural composition of the decision-making activity has been established, which includes problem identification, goal formulation and search for alternative solutions to the problem, decision making, implementation of the decision, control, and evaluation of the result and effectiveness of the solution to the problem. The article describes the system of competencies of the head of an education institution, which consists of cognitive, operational and personal components. The authors have theoretically substantiated and developed a structural model of the activity of the head of an education institution in the area of making and implementing management decisions. The article states that the developed model of the activity of the head of an education institution in making and implementing managerial decisions can be used in the practical activity of the heads of education institutions of different types and forms of ownership.